The Evolving Landscape of Virtual Leadership Research: A Decadal Bibliometric Mapping and Future Directions (2015–2025) - Yuliana Ramawati (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
The rapid shift to remote work and digital collaboration has left the consolidation of virtual leadership theories behind, so that the concept structure, research collaboration patterns, and direction of development of this field are still fragmented in various studies that run separately. Previous bibliometric research has only mapped publication trends or theme clusters separately, no one has yet combined the collaborative network of authors, institutions, and countries with theme mapping in one complete analysis, so it is difficult to see how contributors and research themes develop along with this gap is answered by this study by analyzing 688 Scopus indexed articles for the period 2015–2025 using Bibliophagy to analyze the performance of publications and VOSviewer to map collaboration networks as well as keyword co-occurrences. As a result, the number of publications jumped sharply from 12 articles in 2015 to 252 articles in 2025, and this field is divided into four main theme clusters: communication and remote work management; digital leadership, organizational innovation, and sustainable performance; digital leadership competencies and employee welfare; and digital transformation and artificial intelligence. The chronological mapping shows a clear shift from operational issues in virtual teams to strategic issues such as digital maturity, organizational culture, and innovation capabilities, indicating that virtual leadership is now a multidimensional strategic capability rather than merely a technology-assisted leadership practice. Further research is suggested using longitudinal and multilevel designs to examine how trust, psychological safety, and digital fatigue affect the effectiveness of virtual leadership across various cultural and sectoral contexts, and to integrate these bibliometric results with systematic reviews and meta-analyses to validate the structure of the identified themes.